Combined Posterior and Anterior Ankle Arthroscopy - Peter E. Scholten; C. Niek van Dijk (Case Reports in Orthopedics)
Treatment of combined anterior and posterior ankle pathology usually consists of either combined anterior and posterior arthrotomies or anterior ankle arthroscopy with an additional posterolateral portal. The first technique bears the risk of complications associated with the extensive exposure, the latter technique provides limited access to the posterior ankle joint. A case is described of combined anterior and posterior arthroscopy, with the patient lying prone and then turned supine, addressing both anterior and posterior ankle pathologies in one tempo. This minimally invasive combined approach allows quick recovery and early return to work and sports activities.